The ups and downs of negative (and positive) selection of B cells - Weill, Jean-Claude (J Clin Invest, 2015)
Central and peripheral tolerance checkpoints are in place to remove autoreactive B cell populations and prevent the development of autoimmunity. In this issue of the JCI, Pala and colleagues reveal that individuals with the X-linked immunodeficiency Wiskott-Aldrich syndrome (WAS) have opposite alterations at central and peripheral B cell checkpoints: a more stringent selection for central tolerance, resulting in reduced numbers of autoreactive cells at the emergent immature B cell stage, and a relaxed selection for peripheral tolerance, resulting in an increased frequency of autoreactive cells in the mature naive B cell compartment. Moreover, reinstatement of the WAS gene in these patients restored both B cell tolerance checkpoints. These results suggest that, in a normal situation, mature naive B cells undergo a positive selection step driven by self-antigens, kept in control by Tregs.